A Comparative Study Between Javanese and Madurese Reduplication - Maryani Maryani (Muhammadiyah University of Mataram, 2022)
The purpose of this study is to find out the similarities and differences both in the form and the function of the reduplication between Javanese and Madurese. This research used descriptive qualitative method. The data were taken from Javanese and Madurese words. Madurese words will be collected randomly from some respondents who came from Madura, especially taken from daily conversation in the domain of the family. And discourse in Madurese folktale. Whereas, Javanese words will be taken randomly from Djaka Lodang magazine edition of Desember 2020, November 2021, Januari 2022 and some informants who come from Java especially in Bantul-Yogyakarta. The result showed that there were some similarities between Javanese and Madurese reduplication in the forms, such as: full reduplication, partial reduplication, reduplication combined with affixation, reduplication with sound modification and the word resembles of reduplication. While in the function have two types, i.e. inflective reduplication and derivative reduplication. Meanwhile, for the differences of reduplication, Javanese does not have the forms of final syllable reduplication, whereas Madurese does have and it is very dominant in daily conversation both in the formal or informal situation. The functions of reduplication, Javenese has class word Noun to be Adjective, whereas Madurese does not have.